"It was a brilliant time" : an investigation into the experiences of the founder group of the Directorate of Special Operations - Geyer-van Rensburg, Karen Helen (Rhodes University, Faculty of Commerce, Investec Business School, 2004)
The President, Thabo Mbeki, established the Directorate of Special Operations (DSO) in 1999 shortly after the general elections. The DSO was intended to supplement the efforts of the South African Police Services in combating crime. The unit would concentrate on national priority crimes and police corruption and would report to the National Director of Public Prosecutions (NDPP). The founder members of the DSO were identified in my research and open-ended interviews were conducted with them. The goal of my research was to understand the founder group's experience of the creation of the organisational culture of the DSO and what that experience meant to them . In particular, I wanted to establish what role the founder members of the DSO believed their values and beliefs played in creating the organisation's culture, and their perception of how those values influenced the leadership, management and organisation processes of the DSO. The public sector environment seldom offers opportunities to create something new and this was a unique experience. The founder members received no personal gain except the satisfaction of creating something that would be there for their descendants, something that would change the face of law enforcement forever and in fact, pioneer the troika methodology for the first time in the world within a permanent structure. The values of the founder members influenced their decision to join and they believed that the DSO would make a difference in the lives of ordinary South Africans. They were dedicated, committed, loyal and passionate. Their leadership inspired the members of the organisation and ensured the success of the DSO, despite the lack of resources, staff and legislation. This was an exciting time in the history of the organisation and many personal sacrifices were made. The founder members are proud of the achievements of the DSO and of having been a part thereof. It certainly was "a brilliant time".
Keywords: National Prosecuting Authority of South Africa; South Africa -- Directorate of Special Operations; Crime -- South Africa; Crime -- Prevention -- South Africa; Criminal Justice, Administration of -- South Africa